DEVELOPING SPELLING SKILLS BY ORGANIZING COOPERATIVE LEARNING, LT TECHNIQUES, TOGETHER WITH SKILL EXERCISES FOR PRATHOM SUKSA 3 STUDENTS IN PHRA NAKHON SI AYUTTHAYA EDUCATIONAL SERVICE AREA OFFICE 1 - Jamnongboon, Karnkamon; Techawattanasiridamrong, Watcharapat (Journal of Educational Review Faculty of Education in MCU, 2024)
The purposes of this research article are to 1) compare academic achievement 2) study spelling skills by organizing cooperative learning, LT techniques together with exercises during after class with the specified criteria of 70 percent 3) study the Student satisfaction Using an experimental research format: One-Group Pretest-posttest Design. The tools used in the research include 1) an academic achievement test, 2) a skills training test, and 3) a satisfaction assessment test. The sample group used in the research is: The researcher used group random sampling. There were 28 students in Prathom 3 at Wat Hantra School (Wech Saman Rathanukul). Data analysis and statistics used included mean, standard deviation, and t-test. The results of the research found that; 1) The results of the study of academic achievement before school and after school by organizing cooperative learning, LT techniques, together with skill training exercises of 3rd grade students under the Primary Educational Service Area Office. Study of Phra Nakhon Si Ayutthaya District 1 found that academic achievement scores after studying higher than before studying Statistically significant at the .05 level. 2) The results of the study of spelling skills by organizing cooperative learning, LT techniques, together with skill training of 3rd grade students during the post-study criteria. set to be 70 percent, it was found that students had spelling skills through cooperative learning, LT techniques combined with skill training, accounting for 27.04 percent, higher than 70 percent, with statistical significance at the .05 level and 3) Results of the study of student satisfaction with learning activities in the Thai language subject using cooperative learning, LT techniques combined with exercises. It was found that students were satisfied with the learning activities in the Thai language subject. By organizing cooperative learning, LT techniques combined with skill training, which overall has the highest average level.